PEMBANGUNAN BERKELANJUTAN DAN PERAN STRATEGIS KELOMPOK BISNIS INDUSTRI - Isnaeni, Nurul (Global: Jurnal Politik Internasional, 2002)
This article is aimed to discuss the role and position of the business and industrial groups in the sustainable development agenda. It addresses the question of, in relation to their capitalistic nature of, their potentials and participation in the implementation of sustainable development. The article is aimed to give contextual understanding about the essential dilemma concerning the role of the business and industrial groups (as economic actors) and concludes that strategic partnership is a central issue to be considered in viewing their role the sustainable development agenda.